Changes in intestinal alkaline phosphatase activity in cholera toxin-treated rats. Issue 6 (June 1982) - Miura, S; Asakura, H; Morishita, T; Hibi, T; Munakata, Y; Kobayashi, K; Tsuchiya, M
Abstract : It is conceivable that brush border enzyme activities of the intestinal mucosa will change when bacterial toxins are exposed to the intestinal microvillous membranes. The effect of cholera toxin on the activity of intestinal alkaline phosphatase in rats was therefore determined in the intestinal mucosa by the histochemical method as well as in intestinal lymph by using lymph fistulated-rats. Activity of intestinal alkaline phosphatase in the intestinal mucosa and lymphatics changed biphasically after the oral administration of cholera toxin to rats. For the first three hours after the administration of cholera toxin it was depressed; it then increased and at eight hours reached a maximum. These changes in the activity of intestinal alkaline phosphatase were prevented by the administration of chlorpromazine, a known inhibitor of adenylate cyclase activity.